Polarized training has greater impact on key endurance variables than threshold, high intensity, or high volume training - Stöggl, Thomas; Sperlich, Billy (Frontiers in Physiology, 2014)
Endurance athletes integrate four conditioning concepts in their training programs: high-volume training (HVT), ‘threshold-training’ (THR), high-intensity interval training (HIIT) and a combination of these aforementioned concepts known as polarized training (POL). The purpose of this study was to explore which of these four training concepts provides the greatest response on key components of endurance performance in well-trained endurance athletes. Methods: Forty eight runners, cyclists, triathletes and cross-country skiers (peak oxygen uptake: (VO2peak): 62.6±7.1 mL∙min-1∙kg-1) were randomly assigned to one of four groups performing over nine weeks. An incremental test, work economy and a VO2peak tests were performed. Training intensity was heart rate controlled. Results: POL demonstrated the greatest increase in VO2peak (+6.8 ml∙min∙kg-1 or 11.7%, P< 0.001), time to exhaustion during the ramp protocol (+17.4%, P< 0.001) and peak velocity/power (+5.1%, P< 0.01). Velocity/power at 4 mmol∙L-1 increased after POL (+8.1%, P< 0.01) and HIIT (+5.6%, P< 0.05). No differences in pre to post changes of work economy were found between the groups. Body mass was reduced by 3.7% (P< 0.001) following HIIT, with no changes in the other groups. With the exception of slight improvements in work economy in THR, both HVT and THR had no further effects on measured variables of endurance performance (P>0.05). Conclusion: POL resulted in the greatest improvements in most key variables of endurance performance in well-trained endurance athletes. THR or HVT did not lead to further improvements in performance related variables.